Assessing the Future of Printed Newspaper in Bangladesh: A Factor Analysis Approach - Paul, Jillur Rahaman (Bodhi: An Interdisciplinary Journal, 2025)
In Bangladesh, readers are becoming increasingly accustomed to online news portals, indicating a shift in reading habits. A key question is how the future of printed newspapers will unfold in the coming years. This study examined the relationships among nine variables influencing printed newspaper reading habits and attitudes toward digital alternatives using chi-square (χ²) tests for independence at α = .05. Data were collected from 396 respondents from the Mymensingh administrative division of Bangladesh. Findings indicate a weak but significant link between reading habits and reading medium (Φ = .134), while a strong relationship was observed between subscription and expectation fulfillment (Φ = .382). Reading habits showed a moderate association with the level of satisfaction (Φ = .283), with irregular readers reporting greater satisfaction than regular readers of printed newspapers. A separate test revealed a weak relationship between reading habits and satisfaction with online newspapers (Φ = .183). The strongest relationship was found between print survival and profit-making ability (Φ = .565). A weak negative relationship was observed between perceived ease of use and expectation fulfillment (Φ = −.134). These findings highlight the evolving dynamics between traditional print media and emerging digital platforms, suggesting that printed newspapers face increasing challenges to their longterm sustainability. Keywords: printed newspaper, factors, chi-square (χ2) test, association of variables.